2008
DOI: 10.1128/aem.01855-07
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and Validation of Methods To Quantify Cry1Ab Toxin from Bacillus thuringiensis for Standardization of Insect Bioassays

Abstract: Standardization of toxin preparations derived from Bacillus thuringiensis (Berliner) used in laboratory bioassays is critical for accurately assessing possible changes in the susceptibility of field populations of target pests. Different methods were evaluated to quantify Cry1Ab, the toxin expressed by 80% of the commercially available transgenic maize that targets the European corn borer, Ostrinia nubilalis (Hübner). We compared three methods of quantification on three different toxin preparations from indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 18 publications
1
43
0
Order By: Relevance
“…1). Crespo et al (2008) compared SDS-PAGE, ELISA and Bradford assays for estimating Cry1Ab concentrations in production batches and found that Bradford assays had the lowest coefficient of variation. However, this method did not allow determining whether a Cry1Ab protein in a production batch is really stable or degraded, because it is not possible to differentiate between active Cry1Ab proteins and its degradation products.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…1). Crespo et al (2008) compared SDS-PAGE, ELISA and Bradford assays for estimating Cry1Ab concentrations in production batches and found that Bradford assays had the lowest coefficient of variation. However, this method did not allow determining whether a Cry1Ab protein in a production batch is really stable or degraded, because it is not possible to differentiate between active Cry1Ab proteins and its degradation products.…”
Section: Discussionmentioning
confidence: 99%
“…These batch-to-batch differences could be caused by different treatments during production of these batches and/or differences in the concentration of Cry1Ab depending on the protein determination methods. Crespo et al (2008) noted that different protein batches should be produced and measured with standardized methods in order to eliminate the difference in their activity. When using the same standardized production and quantification methods, bioassay of three different Cry1Ab batches produced in E. coli and B. thuringiensis showed no significant difference in LC 50 values (Crespo et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ELISA methods are the method of choice for the analytical determination of Cry type lectins (Grothaus et al, 2006;Huber-Lukac, Luthy, & Braun, 1983;Walschus, Witt, & Wittmann, 2002;Wang et al, 2007), but other immunoanalytical formats, for example, dot blot (Tapp & Stotzky, 1995), lateral flow immunostrips (Ermolli et al, 2006a), microsphere-based immunoassay (Ermolli et al, 2006b;Fantozzi et al, 2007) or immunomagnetic electrochemical sensor (Volpe, Ammid, Moscone, Occhigrossi, & Palleschi, 2006) have also been reported. ELISAs are widely used for Cry toxin detection in microbial preparations (Crespo et al, 2008;Takahashi et al, 1998) and in GM plants or food (Adamczyk, Adam, & Hardee, 2001;Baumgarte & Tebbe, 2005;Bruns & Abel, 2003;Chen et al, 2009;Chilcutt & Tabashnik, 2004;Douville et al, 2005;Ezequiel, Reggiardo, Vallejos, & Permingeat, 2006;Harwood, Wallin, & Obrycki, 2005;Margarit, Reggiardo, Vallejos, & Permingeat, 2006;Mendelsohn, Kough, Zigfridais, & Matthewsm, 2003;Nguyen & Jehle, 2007;Sims & Berberich, 1996;Stave, 1999Stave, , 2002Xie & Shu, 2001;Zwahlen, Hilbeck, Gugerli, & Nentwig, 2003). Commercial ELISA kits are available and used frequently for detection of Cry toxins from B. thuringiensis or GM plants.…”
mentioning
confidence: 99%